MEDIASI DALAM SENGKETA KETENAGAKERJAAN: STUDI KASUS PT. FREEPORT INDONESIA - Okprianti, Reny; Emilson, Nur Husni; Purwasi, Oktariani; Widiyanti, Nabila Okta (The Juris, 2024)
Labor disputes at PT Freeport Indonesia have become a major problem for industrial relations in the mining sector, especially those related to termination of employment and demands for workers’ rights. This study investigates how effective mediation is as an alternative dispute resolution (ALSR) at PT Freeport, Indonesia. According to Article 1 number 10 and Article 6 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes, mediation is considered a fast and effective method of dispute resolution. This study uses a qualitative methodology, using case studies and data from trusted legal journals and official reports, and finds that mediation at PT Freeport has succeeded in protecting workers’ rights while avoiding litigation processes that can worsen employment relations. This study supports mediation as an effective and fair way to resolve labor disputes in the mining sector.